An improved legibility guideline for text in web pages - Ahmad Affendi, Hashim (2015)
Delivering information through the Internet is universal, offering significant advantages in terms of accessibility and flexibility in designing the appearance of text on the World Wide Web. Video Display Terminal (VDT) technology has recently been equipped with higher and higher pixel densities, and it is important to ensure that the text display as legible and as comfortable as low resolution VDTs. The purpose of this research is to investigate the VDT resolutions that affect reading performance in terms of legibility and comfortability. A reading task based experiment was conducted to measure the level of legibility and comfortability focusing on four texts in the web pages design parameters: the type of fonts, font sizes, colour combinations, and colour contrast ratio between text and background colour. Two sets of experiments were carried out using the selected VDT resolutions for low and high resolutions. The experiments were intended to investigate the relationship between legibility performance and VDT resolutions using reading and word counting tasks. Assessing the comfortable level, subjects then rated their comfort level based on experience doing the reading and word counting task. Improvement was observed almost on all text in the web design parameters when high resolution is used. Legibility levels between the two resolutions tested on type of fonts, font sizes, and colour combinations were not significant. However, in terms of colour contrast ratio, significant improvement was noted. The recommended colour contrast ratio is decreasing (2.35:1) compared to selected low resolution and recommendation from existing guideline (3.32:1). The decrease on colour contrast ratio value will lead to more flexibility in choosing the colour combination of text and background. Prototype Legibility Assessment Tool (LAT) was developed using the improved Legibility Guideline (LG) based on the results of this research. The purpose of this tool is to assess the existing web page legibility level and as a contribution from this research. A black box testing was done to the LAT by comparing the output from the LAT and the output from two web browser selected, Firefox and Internet Explorer. The result is 100% accuracy. Based on the result of the testing also indicate 100% accurate when assessing the text on the web font properties against the newly improved LG.